2015
DOI: 10.1007/s00018-015-2057-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the tyrosine phosphatase STEP61 restores BDNF expression and reverses motor and cognitive deficits in phencyclidine-treated mice

Abstract: Brain-derived neurotrophic factor (BDNF) and STriatal-Enriched protein tyrosine Phosphatase 61 (STEP61) have opposing functions in the brain, with BDNF supporting and STEP61 opposing synaptic strengthening. BDNF and STEP61 also exhibit an inverse pattern of expression in a number of brain disorders, including schizophrenia (SZ). NMDAR antagonists such as phencyclidine (PCP) elicit SZ-like symptoms in rodent models and unaffected individuals, and exacerbate psychotic episodes in SZ. Here we characterize the reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 69 publications
3
23
0
Order By: Relevance
“…TC‐2153 treatment reverses the biochemical, electrophysiological and cognitive deficits in mouse models of schizophrenia and in glutamatergic neurons derived from human‐induced pluripotent stem cells from schizophrenic patients (Xu et al ). As expected, TC‐2153 acutely increases ERK phosphorylation in vivo (Xu et al ,b).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…TC‐2153 treatment reverses the biochemical, electrophysiological and cognitive deficits in mouse models of schizophrenia and in glutamatergic neurons derived from human‐induced pluripotent stem cells from schizophrenic patients (Xu et al ). As expected, TC‐2153 acutely increases ERK phosphorylation in vivo (Xu et al ,b).…”
Section: Introductionsupporting
confidence: 68%
“…For example, STEP activity is elevated in human post‐mortem samples and in animal models of Alzheimer's disease (Snyder et al ; Kurup et al ), Parkinson's disease (Kurup et al ) and schizophrenia (Xu et al ). Moreover, inhibition of STEP with systemic injections of the novel, relatively selective inhibitor, TC‐2153, significantly improves memory deficits in a mouse model of Alzheimer's disease (Xu et al ) as well as phencyclidine‐induced hyperlocomotion in mice (Xu et al ). TC‐2153 treatment reverses the biochemical, electrophysiological and cognitive deficits in mouse models of schizophrenia and in glutamatergic neurons derived from human‐induced pluripotent stem cells from schizophrenic patients (Xu et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous findings 12, 38 suggested that genetic reduction of STEP was sufficient to reduce the biochemical and behavioral changes induced by the NMDAR antagonist PCP. To further demonstrate that pharmacological inhibition of STEP was sufficient to ameliorate the behavioral effects arising from NMDAR antagonism, we used another NMDAR blocker, MK-801, which has been widely validated as a pharmacological model of SZ and induces motor and cognitive deficits in mice 39-41 .…”
Section: Resultsmentioning
confidence: 91%
“…154 In vitro selectivity experiments on full length PTPs revealed that TC-2153 is more potent on isoforms of STEP, STEP 46 (IC 50 = 57 nM) and STEP 61 (IC 50 = 93 nM), compared to highly related PTPs, PTP-SL (IC 50 = 220 nM), and HePTP (IC 50 = 363 nM). It showed even greater selectivity over SHP2 (IC 50 = 6,896 nM) and PTP1B (IC 50 = 723 nM).…”
Section: Covalent Ptp Inhibitorsmentioning
confidence: 99%